Efektivitas Pengadaan Barang dan Jasa Oleh BUMDes dalam Meningkatkan Pendapatan Asli Desa - Regi Refian Garis; Aan Anwar Sihab; Windi Ayu Tiarani (Musamus Journal of Public Administration, 2020)
Based on the results of observations, it is known that there are several problems in the effectiveness of the procurement of goods and services by Hegardanadyaksa Village-Owned Enterprises in increasing the Original Income of Hegarmanah Village, Cidolog District, Ciamis Regency. This research uses descriptive qualitative research method, the length of this research is 10 months with the technique of collecting data through library research, field studies, observation, and interviews. The primary data sources in this study were 14 people. Data processing techniques / data analysis through data reduction, data presentation, and drawing conclusions. Based on the results of the study it can be concluded that: 1) The effectiveness of the procurement of goods and services by Hegardanadyaksa Village- Owned Enterprises in increasing the Original Income of Hegarmanah Village, Cidolog District, Ciamis Regency has not been carried out properly because there are still obstacles to be faced, this is due to lack of direction to the management, low compliance and obedience of the board in carrying out their duties. 2) The obstacles faced are low human resources, low compliance and obedience of administrators in carrying out their duties, lack of direction to the management, price competition and business competition and there is still a tug of interest. 3) The efforts made are including the board in educational activities and training seminars and workshops and providing regular guidance to the board, adding venture capital and improving the quality of goods and service quality, inviting all administrators to be willing to be placed in any position and inviting all administrators to more appreciating and respecting the determination of positions, recruiting managers as needed, providing guidance to administrators.